2018
DOI: 10.29303/aca.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the binding selectivity of 18-membered azacrown ethers with alkaline earth metal species

Abstract: The binding selectivity of 18-membered azacrown ethers (monoaza-N1, diaza-N2, triaza-N3, tetraaza-N4, pentaaza-N5, and hexaaza-18-crown-6 N6) with Ca 2+ , Sr 2+ , Ba 2+ have been studied by density functional theory (DFT) calculations. The complex binding selectivity was analyzed in term of interaction energies, thermodynamic properties, second order interaction energies, and charge transfer effects. The geometrical study shows that Ca 2+ and azacrown complexes acquire envelope like structure, leading to short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It has been shown that some earth alkaline metals have binding affinities towards crown cavities, and that derived from 18C6 macrocycles in particular. [47][48][49]52 We therefore tested aqueous solutions of Ba 2+ salt. The ionic radius of barium of 135 pm, compares well with the ionic radius of K + (138 pm).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that some earth alkaline metals have binding affinities towards crown cavities, and that derived from 18C6 macrocycles in particular. [47][48][49]52 We therefore tested aqueous solutions of Ba 2+ salt. The ionic radius of barium of 135 pm, compares well with the ionic radius of K + (138 pm).…”
Section: Resultsmentioning
confidence: 99%